BRAIN DRAIN: THE BANE OF AFRICAN UNDERDEVELOPMENT - Adejo Godwin; Adejor Idoga; Ebelogu Destiny Ubadinma; Iyorhe Ephraim Shagba; Onita Cyprian Chidebe (PT. Antis International Publisher, 2026)
Objective: Brain Drain is defined as the large scale emigration of highly skilled and educated individuals from developing nations, remains a critical factor contributing to Africa’s underdevelopment. The paper examines how the persistent loss of talent weakens key sectors including healthcare, education, and Public Administration, resulting in reduced productivity and poor service delivery in many African countries. Method: The paper adopts dependency theory as its theoretical framework as put forward by Andre Gunder Frank. Frank believed that the world is divided into core (developed countries) and periphery (developing countries), and that underdevelopment in poorer countries is the result of their historical and economic dependence on richer countries. Results: The shortage of qualified personnel exacerbates poverty, limits innovation, and hinders sustainable development. Furthermore, the financial investment made by government in educating these professionals yields little return, as the benefits are transferred to host countries. Despite some potentials advantages, such as remittance and knowledge transfer through diaspora networks, the negative impacts of brain drain outweigh its benefits. Novelty: The way forward/recommendation is that all hope for development in Africa is not lost, but deliberate efforts must be made by African state to define in clear terms their development objectives, improve local working conditions, increase investment in infrastructure, promote political stability, and create opportunities for professional growth within the continent.